Effective role of mineral oil and biological nanomaterial on thermal energy influenced by magnetic dipole and nanoparticle shape - Nazir, Umar; Sohail, Muhammad; Naz, Samaira; Mukdasai, Kanit; Singh, Manoj; Singh, Abha; Mohan, Chandika Rama; Eldin, Sayed M.; Galal, Ahmed M. (Frontiers in Materials, 2023)
This study of synovial fluid was conducted by considering two different nanofluid models over a two-dimensional stretched surface using nanoparticles of different shapes. We obtained remarkable results regarding the impact of nanoparticles on thermal performance. Through this study, we assessed heat and mass transfer and the involvement of magnetic dipole of chemically reactive species in two-dimensional steady incompressible flow. Heat generation was incorporated in the energy equation and a first-order chemical reaction was involved in the mass transport phenomenon. The concept of boundary layer was adopted to derive the physical problem in Cartesian coordinates, with results in the form of coupled partial differential equations (PDEs). The derived PDEs were highly non-linear, and exact solutions were not possible. Therefore, the PDEs were converted into non-linear ordinary differential equations (ODEs) using appropriate similarity transformation and then solved numerically via the finite element method. The impact of numerous emerging parameters on the solutions are displayed graphically, and the physical significance is discussed. An increment in Sc,Kc, and γ decelerated the solute field, while the concentration gradient increased with enhancement in Sc. Maximum acceleration in velocity for model-I was produced compared to acceleration in the velocity field for model-II.